Activity of the COVID-19 pathogen transmission mechanism and means of its interruption in modern conditions - Podavalenko, Alla Pavlivna; Zhalko-Titarenko, Valentin Porfirovich (Annals of Mechnikov's Institute, 2020)
Introduction. During the 21st century, three coronavirus-related pandemics have been reported. In 2019, a new virus called severe acute coronavirus 2 syndrome (SARS-CoV-2) was confirmed. Currently, the incidence of COVID-19 is growing daily and fatalities are registered in many parts of the world, including Ukraine. The introduction of quarantine somewhat halted the spread of the virus, but led to enormous economic losses. Therefore, the introduction of personal protective equipment could help break the chain of the COVID-19 epidemic process. However, misconceptions about the transmission mechanism of SARS-CoV-2 and myths about personal protective equipment have led the population of Ukraine, including medical workers, to ignore the routine wearing of masks and respirators indoors and in transport, and to keep a distance of 1.5 - 2 meters. Therefore, the purpose of the work was to study the aerosol-aspiration mechanism of transmission of the SARS-CoV-2 virus based on extrapolation from experimental studies and proof of the effectiveness of personal protective equipment in interrupting the transmission of the pathogen COVID-19. Material & metods. The results of an experimental study of the mechanism of transmission of pathogens through the air in the laboratory of the State Institution "Institute of Epidemiology and Infectious Diseases. L.V. Gromashevsky National Academy of Medical Sciences of Ukraine ". The motion of the aerosol cloud and its vorticity was recreated. The formulas were used to determine the aerodynamic characteristics of the process, in particular, time, distance, speed, acceleration and deceleration, cutting size, aspiration flows and directions of aerosol cloud movement. The risk of infection in a mobile atmosphere compared to a stationary indoor atmosphere was calculated using a certain formula, which included the number 3.14; the distance between a sick (or carrier) and a healthy person; a factor of 0.4 that is equal to the maximum diameter ("diameter") of the aerosol cloud. Results & discussion. The mechanism of transmission of the causative agent of infectious diseases is realized through three stages - the isolation of the pathogen from the body, its stay in the factors of transmission and entry into a new organism. It was found that during expiratory acts, the droplets do not scatter in a cone, but are released in separate portions - aerosol clouds of irregular shape about 40 cm in diameter. The movement of these clouds is characterized by a fading inertial run up to 90 cm long, and having overcome this distance, they fall into nearby air currents and, depending on the direction of the wind, can move in different directions. In a closed room, on the way of its movement, an aerosol cloud changes within 1 - 7 seconds. Super-large droplets in the range of 500 - 1000 microns fly about 1 meter per second along ballistic curves and fall to the floor, slightly smaller droplets with a radius of 50 - 100 microns have time to dry out, decrease in diameter and settle within the next few seconds. Droplets in the 25 - 50 micron range settle in two and a half minutes, and even smaller droplets can stay in the air for tens of minutes or even hours. In confined spaces, the ventilation flows directed towards the exhaust hood can prevent transmission of SARS-CoV-2 coronavirus. There is a misconception that it is not possible to become infected with the SARS-CoV-2 virus outdoors. The study showed that the risk of infection in the open at a distance of 1 meter is 12%, at a distance of 2 and 4 meters, respectively, 6.3% and 3.3%. The rapid spread of the COVID-19 pandemic against the background of the susceptible population contributed to the smoothing of annual seasonality, but its pronounced manifestation in the long-term dynamics is not excluded. Large dispersed droplets have been shown to settle mainly in the upper respiratory tract and cause subclinical forms with symptoms of acute respiratory viral infection and carrieris, while small ones can enter the lower respiratory tract, causing severe acute pneumonia. The chain infectious process is dose-dependent, and is largely determined by the nature of the pathogen. The pattern of dose-dependence of the infectious process is especially important for understanding the epidemic and infectious processes in COVID-19. The two-week incubation period suggests that the coronavirus population may grow rather slowly. Therefore, it can be assumed that in the current COVID-19 epidemic process, SARS-CoV-2 virus infection occurs at doses close to those that cause the carrieris, ie relatively small doses. And the conversation is a variant of the aerosol-aspiration mechanism of transmission of the pathogen, which causes the transmission of small doses, and hence the pandemic spread of asymptomatic and subclinical forms of coronavirus infection. Therefore, in our opinion, the most adequate and effective means of protection against COVID-19 is the routine use of masks and respirators that meet the State Standard of Ukraine. Conclusion. The spread of COVID-19 occurs through aerosol clouds mainly indoors (buildings, structures, transport), but the risk of infection also remains on the street and in parks where there are crowds. The severity of the disease depends on the loading of the aerosol cloud with the SARS-CoV-2 virus, the dose and characteristics of the aerosol droplets that enter the body. Large droplets, which get into the body when talking, even in small doses, cause subclinical forms and carriers, and fine - severe forms of COVID-19. Total mask regimen interrupts the aerosol-aspiration mechanism of SARS-Cov-2 transmission by stopping its transmission from a COVID-19 patient to a healthy person. DOI: 10.5281/zenodo.4382233